Characterization of biocontrol agents isolated from the leaves of mangroves grown in Sampiran Beach, North Sulawesi, Indonesia againts damping-off of cucumber - Yuliar Yuliar; Suciatmih Suciatmih (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2017)
Bacterial biocontrol isolates MND61, MND63, and MND65 were originally isolated from mangrove leaves of Derris trifoliata Lour, Sonneratia alba J. Smith, and Avicennia marina (Forsk) respectively grown in Sampiran beach, North Manado, North Sulawesi island, Indonesia. They were evaluated on suppression of cucumber damping-off. Identification results showed that based on 16S rRNA sequence, MND61 isolate had 99% similarity to Kleibsiella pneumoniae ATTCC13884T, MND63 isolate had 98% similarity to Bacillus cereus NENA11, and MND65 isolate had 98% similarity to Bacillus subtilis jllsy. Results of greenhouse test showed that MND61 and MND63 suppressed Pythium aphanidermatum damping-off of cucumber significantly (P < 0.005) by 73-80%. Cocultures of these two biocontrol agent in potato dextrose broth also suppressed the pathogens population about 5-46 %. MND61 isolate produced indole acetic acid, in contrary to MND63 and MND65 isolates did not. The inhibitory assay effect of broth culture of MND61, MND63, and MND65 isolates to phytopatogenic fungi Fusarium oxysporum, P. aphanidermatum, P. ultimum, Rhizoctonia solani, Pyricularia oryzae and Xanthomonas oryzae in PDA plate indicated that two strains (MND63 and MND65) inhibited the growth of F. oxysporum, and R. solani growth, otherwise MND61 isolate did not inhibit the growth of any phytopatogenic assay.